Contrast-Enhanced Ultrasound Findings of Hepatocellular Carcinoma With Neuroendocrine Carcinoma: A Case Report - Wang, Hong; Yang, Dan; Wu, Zhenru; Luo, Yan; Ling, Wenwu (Frontiers in Medicine, 2021)
Hepatocellular carcinoma (HCC) with the concurrent occurrence of primary hepatic neuroendocrine carcinoma (NEC) of the liver is extremely rare. Preoperative diagnosis of HCC combined with NEC is very difficult. Here, we presented a case report of HCC combined with NEC. A 33-year-old male was admitted to our hospital due to focal liver lesion. To further the diagnosis, he received laboratory tests, conventional ultrasound, contrast-enhanced ultrasound (CEUS), and magnetic resonance imaging (MRI). Grayscale ultrasound showed a hypoechoic nodule with peripheral hypoechoic halo and central small patches of anechoic area in the hepatic segment VI, and the liver background was cirrhosis. In the CEUS, the solid component of the nodule was rapidly homogeneous hyper-enhancement in the arterial phase. Then, the enhancement of the nodule was washed out slowly and gradually; the nodule presented heterogeneously mild enhancement in the portal phase, and slight hypo-enhancement was showed in the late phase. The hypo-enhanced area was mainly located in the surrounding space. Meanwhile, there was a small piece of non-enhanced area within the lesion center in the whole three-phase imaging. MRI showed a lobular contoured mass in segment VI. The patient underwent middle liver resection, splenectomy, and cholecystectomy. The pathological diagnosis was a HCC with NEC. At the time of the preparation of this manuscript, the patient has been alive without recurrence or distant metastases for 6 months since the surgery. We mainly focus on the ultrasound imaging characteristics, especially its enhancement manifestations on CEUS. In this report, since this article is a case report, which is based on the clinical information of the patient and does not involve the patient's privacy, informed consent is not necessary. In addition, the patient agreed to publish the case. To the best of our knowledge, this report is the first to describe the CEUS patterns of the HCC combined with NEC. Herein, we report a case that provides novel insights that will improve clinicians' awareness of the clinical and ultrasound manifestations of this mixed tumor, resulting in improved diagnosis, treatment, and outcomes.